Effect of flipped classroom on student perceptions, academic scores and study practices - Wali, Othman; Vanka, Shanthi; Vanka, Amit (Journal of Medical Science, 2024)
Aim. To evaluate the educational impact of two flipped classroom models. Material and methods. Traditional lectures were followed by Flipped classroom (FC) with face to face(F2F) session (cohort of 2019-20) and online (cohort 2020-21). Students’ perceptions were collected by questionnaire after lectures and FC. Historic academic scores on selected topic were compared scores after introduction of FC. The learning management system(LMS) was used to monitor student usage of learning resources. Results. Students perceptions for cohort 2019-20 were significantly higher(p>0.05) for FC(F2F) compared to lecture. Students’ perceptions for cohort 2020-21 were also significantly higher for FC(online) compared to online lecture. Academic scores did not show significant difference between lecture and FC. Increased hits on LMS for online resources were associated with FC or summative assessment. Conclusions. Students were overwhelmingly positive on FC for both: with F2F and online , and academic scores were similar to lecture. FC can possibly improve student study habits but needs further research.